INTERPRETASI KRISTUS MERENDAHKAN DIRI BERDASARKAN FILIPI 2:8-11 SEBAGAI MODEL KERENDAHAN HATI JEMAAT TUHAN MASA KINI - Watulingas, Fandri (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Conflicts often occur in God's congregation, whether between leaders and leaders, congregations and leaders or between fellow congregations. If the problem is not handled properly, it can damage the fellowship of God's congregation and can even result in division. The purpose of writing this article is to find out the attitude of Jesus who humbled himself in Philippians 2:8-11 which Paul used to advise God's church in Philippi who were facing problems. The method used in this research is the library method. In this study, it was found that Jesus deliberately took the attitude of humbling himself as low as a servant until he experienced death on the cross, in which death was the most disgusting and shameful death of any death. If every leader and congregation of God follows the example of Jesus who humbled himself, of course, every problem that often arises in the fellowship can be resolved properly.